GnRH therapy in matured Holstein Friesian and Jersey bulls with impaired reproduction - BHASKARAN, R; DUBEY, B MUNILAL (The Indian Journal of Animal Reproduction, 2023)
Effect of GnRH therapy in seven Holstein Friesian (HF) and three Jersey bulls with impaired reproduction aged between 4 and 5 years was investigated. The investigated impaired reproductive condition was ’normal libido with very poor quality and quantity of semen’. Each experimental bull received single injection of 20mg of synthetic GnRH (Buserelin-Acetate Receptal®, Hoechst) for 19 consequent times at four days interval, semen was collected in artificial vagina and subjected for detailed analysis of characteristics. GnRH therapy significantly reduced (P<0.05) the reactions time and increased the semen volume (P<0.0 I) during therapy and post therapy period. pH value was not altered. Per ml concentration and total concentration increased (P<0.01 ). Mean motility of spermatozoa increased significantly ((P<0.0 I) in neat semen and non-significant increase was observed in extended semen during therapy period. Viability of spermatozoa in 6 and 24 hours stored neat and extended semen showed nonsignificant increase. Livability of spermatozoa was not altered by GnRH therapy. Total abnormality decreased significantly during therapy period. However, the improvement in quantitative and qualitative characterstics of semen in the present study was not optimum for cryopreservation of semen.